(untitled) (Journal of Applied Oral Science, 2021)
Laboratory tests are routinely used to test bonding properties of dental adhesives. Various aging methods that simulate the oral environment are used to complement these tests for assessment of adhesive bond durability. However, most of these methods challenge hydrolytic and mechanical stability of the adhesive- enamel/dentin interface, and not the biostability of dental adhesives. Objective: To compare resin-dentin microtensile bond strength (μTBS) after a 15-day Streptococcus mutans (SM) or Streptococcus sobrinus (SS) bacterial exposure to the 6-month water storage (WS) ISO 11405 type 3 test. Methodology: A total of 31 molars were flattened and their exposed dentin was restored with Optibond-FL adhesive system and Z-100 dental composite. Each restored molar was sectioned and trimmed into four dumbbell-shaped specimens, and randomly distributed based on the following aging conditions: A) 6 months of WS (n=31), B) 5.5 months of WS + 15 days of a SM-biofilm challenge (n=31), C) 15 days of a SM-biofilm challenge (n=31) and D) 15 days of a SS-biofilm challenge (n=31). μTBS were determined and the failure modes were classified using light microscopy. Results: Statistical analyses showed that each type of aging condition affected μTBS (p<0.0001). For Group A (49.7±15.5MPa), the mean μTBS was significantly greater than in Groups B (19.3±6.3MPa), C (19.9±5.9MPa) and D (23.6±7.9MPa). For Group D, the mean μTBS was also significantly greater than for Groups B and C, but no difference was observed between Groups B and C. Conclusion: A Streptococcus mutans- or Streptococcus sobrinus-based biofilm challenge for 15 days resulted in a significantly lower μTBS than did the ISO 11405 recommended 6 months of water storage. This type of biofilm-based aging model seems to be a practical method for testing biostability of resin-dentin bonding.